2021
DOI: 10.3389/fpls.2021.678580
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Dynamics of Intracellular Gene Transfer in Plastid Genomes of Viola (Violaceae) and Order Malpighiales

Abstract: Functional gene transfer from organelles to the nucleus, known as intracellular gene transfer (IGT), is an ongoing process in flowering plants. The complete plastid genomes (plastomes) of two Ulleung island endemic violets, Viola ulleungdoensis and V. woosanensis, were characterized, revealing a lack of the plastid-encoded infA, rpl32, and rps16 genes. In addition, functional replacement of the three plastid-encoded genes in the nucleus was confirmed within the genus Viola and the order Malpighiales. Three str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Furthermore, we identified that the genes infA , rpl32 , and rps16 were not present in 17 Viola cp genomes (Table S 1 ). Studies suggest that the cause of the loss of these genes may be due to parallel loss of chloroplast DNA during the evolution of angiosperms [ 45 47 ]. There were 17 intron-containing genes in each Viola species analyzed (Table S 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we identified that the genes infA , rpl32 , and rps16 were not present in 17 Viola cp genomes (Table S 1 ). Studies suggest that the cause of the loss of these genes may be due to parallel loss of chloroplast DNA during the evolution of angiosperms [ 45 47 ]. There were 17 intron-containing genes in each Viola species analyzed (Table S 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the mtDNA had multiple losses of ribosomal and succinate dehydrogenase genes, caused by these genes being transferred to the host cell and becoming part of the nuclear genome during plant evolution [ 16 , 17 ]. Some chloroplast genes were also transferred to the nuclear genome during evolution, which is similar to the mitochondrial gene process [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“… 2019 ), V. selkirkii NC_059909 (unpublished), V. ulleungdoensis NC_050744 (Yang et al. 2021 ), V. albida ON815353 (this study), V. chaerophylloides NC_065000 (Cao et al. 2022 ), V. raddeana NC_041584 (Cheon et al.…”
Section: Resultsmentioning
confidence: 77%
“…However, previous molecular phylogenetic studies of Viola didn’t provide information for the most relative genome to V. albida (Yoo and Jang 2010 ; Yang et al. 2021 ) because trees from these studies showed polytomy or low bootstrap supports. We, therefore, further mapped the raw reads against the three candidate cp genomes [ V. selkirkii (NC_059909), V. chaerophylloides (NC_065000), and V. phalacrocarpa (NC_041583)], respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation